CULTURAL DIFFERENCES IN BUSINESS VALUES PERSPECTIVE AND MANAGER-EMPLOYEE HARMONIZATION - Akbarzada, Tural (Annals of Spiru Haret University. Economic Series, 2022)
In the research, manager-employee harmony is examined in the perspective of business values. Since manager-employee compatibility is the subject of study in the perspective of work values, the values that emerge as a result of the work values of the managers and employees and the work values of the employees regarding their managers are also determined as a prerequisite, since the fit can be determined and guides the research.